GIS-Based Spatial Analysis of Landslide Risk in the Bango Sub-Watershed, Malang Regency - Oktavia, Maharani; Lusiya, Lusiya (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aims to assess and map landslide risk zones in the Bango Sub-Watershed, Malang Regency, by integrating natural physical factors and human activities using a GIS-based spatial analysis to support effective disaster mitigation and regional planning.Methodology: Primary data, including land use patterns, slope excavation, pond and drainage construction, and infrastructure development, were integrated with secondary data such as rainfall records (2005–2014), geological maps, soil type maps, land use maps, and historical earthquake data. Thiessen polygons and overlay techniques were applied in ArcGIS 10.1 to systematically quantify spatial variations in landslide susceptibility across the Bango Sub-Watershed.Main Findings: The results show that most areas in the Bango Sub-Watershed are classified as low to medium landslide risk, while high-risk zones, associated with slopes greater than 40%, are confined to steep terrain with intensive human activity. The integration of environmental factors, including slope, rainfall, and soil type, with anthropogenic activities produces more detailed and reliable spatial risk maps, enabling targeted prioritization for mitigation measures and supporting improved disaster planning and management.Novelty/Originality of this study: This research integrates multiple environmental and human activity datasets into GIS through the use of Thiessen polygons and overlay analysis, offering a more comprehensive and precise assessment of landslide risk than previous studies. The methodology provides a replicable framework for other similar watersheds, supporting enhanced disaster mitigation planning, informed land-use decisions, and evidence-based strategies for reducing potential damage in vulnerable areas.